(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2009)
In the work the results of compression resistance tests of cement soil samples of various initial densities of a skeleton and the cement composition for the time period from 7 to 60 days are discussed. It was established that the influence of initial density of a cement soil skeleton on resistance of compression is insignificant for the initial 7 days. Increase of intensity to resistance of compression in time is observed for the time interval from 7 to 28 days. In the range from 28 to 60 days decrease in intensity of increase of soil samples compression strength was observed. The greatest intensity of strength increase in time on compression test at the optimum structure of cement soil (the cement of 7%) and the maximum compacted conditions were registered. Standard strength on compression (28 days) of cement soil makes only a part of the general strength.